2018
DOI: 10.21744/ijllc.v4n6.427
|View full text |Cite
|
Sign up to set email alerts
|

Repetition in Indonesian political language

Abstract: This is a critical discourse study that tried to reveals repetition phenomena in political language. We conducted the study by examining the language of Soekarno, as an Asian politician, as well as a nation founder and the first president of Indonesia, where this study was conducted on. Data were gained by documentation method, and be analyzed by applying Critical Discourse Analysis theory that proposed by Fairclough. We found that repetition as a language style used by Indonesian politician, in this case, Soe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The occasion is only used by the person to start the commission of the criminal offense. In the analysis of the individual reasons of criminal behavior it is also necessary to consider thirst of criminals for self-justification, reduction of circumstances who allegedly acted as the reason of the commission of the criminal offense (Latupeirissa et al, 2018;Arnawa et al, 2019).…”
Section: The Determinants Of Criminal Behaviormentioning
confidence: 99%
“…The occasion is only used by the person to start the commission of the criminal offense. In the analysis of the individual reasons of criminal behavior it is also necessary to consider thirst of criminals for self-justification, reduction of circumstances who allegedly acted as the reason of the commission of the criminal offense (Latupeirissa et al, 2018;Arnawa et al, 2019).…”
Section: The Determinants Of Criminal Behaviormentioning
confidence: 99%
“…co.id/read/hari-ini-ptun-akan-putuskan-nasib-hidup-hti-di-indonesia The former leader of HTI stated that they still have a lot of supporters in Indonesia (Firmansyah, 2018). State Intelligence Agency of Indonesia stated that the organization of HTI and other Khilafah-secret-organizations 4 are involved in the Indonesian political world (Arigi, 2019;Latupeirissa et al, 2018). It means that some Indonesian .…”
Section: Why Indonesia?mentioning
confidence: 99%
“…The procedures proposed, are based on the examination of a political speech delivered by Soekarno 6 . Latupeirissa et al, (2018), have conducted research about Soekarno Political Language and found that Soekarno used language for the sake of Indonesian people. On their research, they applied the theory of Critical Discourse Analysis proposed by Fairclough, (1995Fairclough, ( , 2003Fairclough, ( , 2005Fairclough, ( , 2006.…”
Section: Why Indonesia?mentioning
confidence: 99%